PDZ and LIM Domain-Encoding Genes: Molecular Interactions and their Role in Development - Aartjan J. W. te Velthuis; Christoph P. Bagowski (The Scientific World Journal)
PDZ/LIM genes encode a group of proteins that play very important, but diverse, biological roles. They have been implicated in numerous vital processes, e.g., cytoskeleton organization, neuronal signaling, cell lineage specification, organ development, and oncogenesis.